The Fedathi Sequence and the use of 3D digital technologies as methodological resources for teaching human anatomy: an integrative review (Research, Society and Development, 2020)
Much has been discussed about the methodological resources used in the teaching of human anatomy, in view of the importance that its study results for the practice of the health professional. The objective of this study is to present the Fedathi Sequence and the use of 3D digital technologies as methodological resources in the practice of teaching human anatomy. The research is of a qualitative nature on the relationship and application of methodological resources in / for teaching in the health area. According to the objective, it has a descriptive and exploratory character, using as technical procedures an integrative review in relation to the use of 3D digital technologies, through articles indexed in the electronic databases PubMed, ScienceDirect and Google Scholar, published in Portuguese and English, from 2015 to 2019, considering the following descriptors: digital technologies, teaching, anatomy and learning and in relation to the Fedathi Sequence, we seek to select articles and theses that characterize it. For the analysis, 12 articles were selected in order to allow a detailed visualization on the use of 3D digital technologies in the teaching of anatomy and other 05 academic documents to present the methodology of the Fedathi Sequence as a methodological resource in the teaching of anatomy. The data report that the inclusion of 3D technologies enables better qualification in the teaching in question, in addition to emphasizing the importance of the Fedathi Sequence as a methodological resource to be incorporated in the health area.